Synaptic transmission despite severe hypoxia in hippocampal slices of the deep-diving hooded seal. (15th October 2016) - Geiseler, Samuel J.; Larson, John; Folkow, Lars P.
Highlights: Field excitatory postsynaptic potentials (fEPSPs) were recorded in hippocampal slices of hooded seals, reindeer and mice. fEPSP were observed in seal slices throughout 3 h of hypoxia but disappeared in reindeer and mice after only ∼5 min. fEPSP amplitude increased in reoxygenated seal slices, but did not return in reindeer/mice, even after only 20-min hypoxia. Seal slices displayed attenuated paired-pulse facilitation, in contrast to reindeer and mice slices. Enhanced intracellular Ca 2+ buffering capacity may underlie both the reduced PPF and the high hypoxia tolerance in seals. Abstract: Brain neurons of the deep-diving hooded seal ( Cystophora cristata ) are known to be inherently hypoxia tolerant. Here, we have used in vitro field potential recordings in hippocampal slices to compare effects of severe hypoxia on synaptic transmission in hooded seals vs. non-diving mammals. Synaptic responses of mice ( Mus musculus ) to hypoxia were in accordance with previously published data. Hippocampal slices of reindeer ( Rangifer tarandus ), an alternative large-mammal non-diving model, behaved in a similar way as mouse slices, in that synaptic activity disappeared rapidly without recovery after >20 min in hypoxia. The synaptic activity of hooded seal slices decreased in hypoxia, but unlike mice and reindeer, it remained at >30% of the normoxic amplitude throughout 3 h of severe hypoxia. Also, upon reoxygenation, the signal recovered to ∼50% of the pre-challenge (normoxic) amplitude. The AMPA-type glutamate receptor antagonist CNQX eliminated this signal, showing that it was not an artifact. Paired pulse facilitation (PPF), typically associated with increased presynaptic calcium (Ca 2+ ) levels, was significantly reduced in the seal slices. We propose that the build-up of Ca 2+ concentration is limited in seal presynaptic terminals, possibly due to a high Ca 2+ buffering capacity, which could explain both the attenuated PPF and the remarkable neural hypoxia tolerance of this species. Although we found no significant hypoxia-induced upregulation of mRNA for the Ca 2+ binding proteins calbindin d28k or parvalbumin in hooded seal hippocampal slices, a recent study reports very high transcript levels of the Ca 2+ binding protein S100B in this species, which is in support of the hypothesis.